Calcium isotopes in archaeological bones and their relationship to dairy consumption - Reynard, L; Henderson, G; Hedges, R (Elsevier, 2011)
The calcium isotope ratios (δ44/42Ca) of bones from humans and fauna from three archaeological sites, Taforalt, Abu Hureyra, and Danebury, are evaluated in order to assess whether calcium isotope ratios of bones can be used to detect dairy consumption by adult humans. At each site the fauna δ44/42Ca is the same regardless of species, while the humans have lower δ44/42Ca than the local animals by 0.24-0.41‰ (site means). However we cannot ascribe this difference to dairy consumption, given this human-faunal difference also occurs in Epipalaeolithic and Mesolithic adult humans, where dairy consumption is unlikely. Rather, this difference appears to be a result of differences in metabolic processes or other aspects of diet between humans and fauna. Minimal isotopic change in sequential acid leaches of bone powders and consideration of the high calcium concentration in bone suggest that bone calcium isotope ratios are not substantially affected by diagenetic change.